Use of environmental sensors and sensor networks to develop water and salinity budgets for seasonal wetland real-time water quality manageme nt - Quinn, Nigel W. T.; Ortega, Ricardo; Rahilly, Patrick J. A.; Royer, Caleb W. (Environmental Modelling & Software, 2010)
Management of river salt loads in a complex and highly regulated river basin such as the San Joaquin River Basin of California presents sign ificant challenges for current Information Technology. Computer-based numerical models are used as a means of simulating hydrologic processe s and water quality within the basin and can be useful tools for organ izing Basin data in a structured and readily accessible manner. These models can also be used to extend information derived from environment al sensors within existing monitoring networks to areas outside these systems based on similarity factors – since it would be cost prohibiti ve to collect data for every channel or pollutant source within the Ba sin. A common feature of all hydrologic and water quality models is th e ability to perform mass balances. This paper describes the use of a number of state-of-the-art sensor technologies that have been deployed to obtain water and salinity mass balances for a 60,000ha tract of se asonally managed wetlands in the San Joaquin River Basin of California . These sensor technologies are being combined with more traditional e nvironmental monitoring techniques to support real-time salinity manag ement (RTSM) in the River Basin. Two of these new technology applicati ons: YSI-Econet (which supports continuous flow and salinity monitorin g of surface water deliveries and seasonal wetland drainage); and elec tromagnetic salinity mapping (a remote sensing technology for mapping soil salinity in the surface soils) – have not previously been reporte d in the literature. Continuous sensor deployments that experience mor e widespread use include: weather station sensor arrays – used to esti mate wetland pond evaporation and moist soil plant evapotranspiration; high resolution multi-spectral imagery – used to discriminate between and estimate the area of wetland moist soil plant vegetation; and gro undwater level sensors – used primarily to estimate seepage losses ben eath a wetland pond during flood-up. Important issues associated with quality assurance of continuous data are discussed and the application of a state-of-the-art software product AQUARIUS, which streamlines th e process of data error correction and dissemination, is described as an essential element of ensuring successful RTSM implementation in the San Joaquin River Basin.
Keywords: Environmental decision support; Forecasting; Sensor networks; Sensors; Water quality